Knowledge of pharmacists and parents towards antibiotic use in pediatrics: a cross-sectional study in Lebanon. - ZAHREDDINE, Lama; HALLIT, Souheil; SHAKAROUN, Shadia; AL-HAJJE, Amal; AWADA, Sanaa; LAHOUD, Nathalie (Pharmacy Practice (1886-3655))
Objectives: to assess the knowledge of both parents and community pharmacists regarding antibiotics use and resistance in pediatrics in Lebanon. Methods: A cross-sectional study was conducted between June and August 2017 in community pharmacies. A pre-established questionnaire targeting knowledge of parents and pharmacists regarding antibiotics use/misuse was carried out. An index of knowledge was computed to assess factors associated with good knowledge on antibiotics use/misuse. Results: The study showed that 28.7% of pharmacists did not know which factors may contribute to antimicrobial resistance. Concerning the misuse of antibiotics, pharmacists blamed at first parents (90.1%), at second level physicians (72.8%), and third themselves (59.4%). Furthermore, pharmacists believed that the socioeconomic problems of the country (86.1%), the level of resistance to the molecule of choice (80.8%), the lack of consultation time (71.2%) and the lack of national guidelines/recommendations (66.3%) might be additional factors contributing to antimicrobial resistance. In case of acute otitis media, the majority of pharmacists chose the correct treatment, dose and duration according to international guidelines; this was in contrast to the results obtained in case of pharyngitis. Female pharmacists had a significantly higher knowledge score compared to their male counterparts (ORa=2.51). Half of parents (42.6%) declared that antibiotics act against both viruses and bacteria, 55.9% still believe that the presence of fever requires the administration of antibiotics, 50% didn't know the consequences of antibiotics misuse, 58.4% said that it is okay to give their child antibiotics without a physician's advice or based on a pharmacist's recommendation, and 66.7% trusted the pharmacist in the antibiotic prescription. Parents with a university level of education or a master's degree had significantly better knowledge compared to illiterate ones (ORa=9.04 and ORa=16.46, respectively). Conclusions: Based on the results obtained, it would be necessary to implement educational campaigns in order to increase awareness on antibiotics misuse and resistance in pediatrics.